Trends in suicidal ideation in England: the National Psychiatric Morbidity Surveys of 2000 and 2007. Issue 1 (January 2014) - Spiers, N.; Bebbington, P. E.; Dennis, M. S.; Brugha, T. S.; McManus, S.; Jenkins, R.; Meltzer, H.
<x content-type="archive" xml:space="preserve">Abstract</x> Background Recent falls in suicide rates should be accompanied by a decline in the prevalence of suicidal ideation. Method We used a pseudo-cohort analytic strategy to examine trends in suicidal ideation measured identically in 2000 and 2007, in nationally representative English probability samples of adults aged ⩾ 16 years. Suicidal ideation included tiredness of life, death wishes and thoughts of suicide. Logistic regression models were fitted to estimate trends in age-specific prevalence of suicidal ideation in the past year and past week between 2000 and 2007. Results There were 6799 participants aged 16–71 years in 2000, and 6815 participants aged 16–78 years in 2007. There was little evidence of trends in prevalence of suicidal ideation, with the exception of women aged 44–50 years in 2007, whose prevalence was unusually high. Prevalence of suicidal ideation in the past year followed a W-shaped profile with age, with peaks at the transition to adulthood, in the forties, and in the oldest participants. Conclusions Despite falling suicide rates, suicidal ideation did not decline overall between 2000 and 2007. This may indicate the success of the National Suicide Prevention Strategy. Women aged 44–50 years in 2007 were, however, particularly prone to suicidal ideation. As they also have the highest age-adjusted prevalence of common mental disorders and the highest female suicide rate, there are clear implications for treatment access, availability and delivery in primary care.